Impact of Incremental Methylene Groups on the Energetic Properties of Aromatic Nitramines - Jelena Tamuliene; Jonas Sarlauskas (Energies, 2023)
The investigation of a series of secondary aromatic nitramines was performed to reveal the impact of incremental methylene groups on the stability, shock impulse, and energetic properties of these compounds. Becke’s three-parameter hybrid functional approach with non-local correlation provided by Lee, Yang, and Parr and a cc-pVTZ basis set was used to obtain the geometry, total energy, and heat of formation of the most stable conformers of these aromatic nitramines. These parameters were used to evaluate the density, resistance to shock stimuli, detonation pressure, and velocity of the nitramines under study. Referring to the results obtained, we concluded that the thermal stability and resistance to shock stimuli of the compound investigated was directly CH2 chain length-dependent, while their energetic- properties, such as detonation pressure and velocity, were worsened due to this chain increase. We also found that the stability of the compounds increases more significantly than the worsening energetic properties of aromatic nitramines. The results obtained reveal that in some cases the number of CH2 in the chain should be smaller than three so that the explosive properties of the compounds under study would not be worse than TNT.